Penerapan Model Pembelajaran Role Playing untuk Meningkatkan Kemampuan Komunikasi pada Mata Pelajaran Pendidikan Pancasila - Fitrah Cahyani Tuna; Fandi H. Binggo; Yane Hardiyanti Mahmud (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to improve students’ communication skills through the implementation of the Role Playing learning model in the Pancasila Education subject for fifth-grade students at SDN 2 Botupingge, Bone Bolango Regency. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 15 students. Data collection techniques included observation, interviews, documentation, and tests. Data were analyzed using descriptive quantitative methods by comparing the mean scores and the percentage of learning mastery in each cycle. The results showed that the implementation of the Role Playing model significantly improved students’ communication skills. In the initial observation, learning mastery was only 20%. After the first cycle, it increased to 60%. In the second cycle, learning mastery reached 86.6% with an average score of 78.84. This improvement occurred because students became more actively involved in the learning process, gained confidence in expressing their ideas, and were able to interact effectively through role-playing activities. In conclusion, the Role Playing learning model is effective in improving students’ communication skills in Pancasila Education at the elementary school level.